ORGANIZATIONAL CHANGES: THE PROBLEM OF STAFF RESISTANCE AND WAYS TO OVERCOME IT - Pokotylo , T. V; Smahliuk , A. A (Theory and Practice of Public Administration, 2021)
Public authorities must be able to generate changes in the external environment and the result of such changes must be a system of public administration that will ensure the proper implementation of policy decisions and legal norms, be transparent, aimed at sustainable economic growth and promote entrepreneurship. The implementation of such an important mission puts on the agenda for managers to rethink the form and content of organizational change and develop new approaches to managing them. In order for public authorities to perform their functions successfully, the organization must constantly change itself with a focus on achieving the mission within the current environment, which is becoming increasingly turbulent. The essence of the changes is revealed and the constituent elements of these changes are determined. The role of the leader in the period of organizational changes is considered. When making changes, there is inevitably resistance to change. The main causes of resistance to change in organizations are identified. These causes of resistance cause passive or active resistance to change. The directions of activity of the personnel management service concerning carrying out of organizational changes are offered. The ADKAR model, which can be successfully used in personnel resistance management, is considered. Effective management of the human aspect of change consists of managing the five key phases that underlie ADKAR: A (awareness) - awareness of the need for change; D (desire) - the desire to implement change; K (knowledge) - knowledge (skills); A (ability) - the ability to implement changes; R (reinforcement) - motivation to action (incentives).With this model, you can identify the steps that are needed to increase the effectiveness of change. In working with staff to overcome resistance to change, the following methods have gained practical application: information and communication; participation and involvement; help and support; negotiations and agreements; manipulation and co-optation; explicit and implicit coercion. It is determined that coaching, as a new tool of personnel management is effective in overcoming the resistance of staff, which is focused on improving the efficiency of the employee in the organization.